Enhanced isopropanol–butanol–ethanol mixture production through manipulation of intracellular NAD(P)H level in the recombinant Clostridium acetobutylicum XY16 - Chao Wang (Biotechnology for Biofuels, 2018)
Abstract Background The formation of by-products, mainly acetone in acetone–butanol–ethanol (ABE) fermentation, significantly affects the solvent yield and downstream separation process. In this study, we genetically engineered Clostridium acetobutylicum XY16 isolated by our lab to eliminate acetone production and altered ABE to isopropanol–butanol–ethanol (IBE). Meanwhile, process optimization under pH control strategies and supplementation of calcium carbonate were adopted to investigate the interaction between the reducing force of the metabolic networks and IBE production. Results After successful introduction of secondary alcohol dehydrogenase into C. acetobutylicum XY16, the recombinant XY16 harboring pSADH could completely eliminate acetone production and convert it into isopropanol, indicating great potential for large-scale production of IBE mixtures. Especially, pH could significantly improve final solvent titer through regulation of NADH and NADPH levels in vivo. Under the optimal pH level of 4.8, the total IBE production was significantly increased from 3.88 to 16.09 g/L with final 9.97, 4.98 and 1.14 g/L of butanol, isopropanol, and ethanol. Meanwhile, NADH and NADPH levels were maintained at optimal levels for IBE formation compared to the control one without pH adjustment. Furthermore, calcium carbonate could play dual roles as both buffering agency and activator for NAD kinase (NADK), and supplementation of 10 g/L calcium carbonate could finally improve the IBE production to 17.77 g/L with 10.51, 6.02, and 1.24 g/L of butanol, isopropanol, and ethanol. Conclusion The complete conversion of acetone into isopropanol in the recombinant C. acetobutylicum XY16 harboring pSADH could alter ABE to IBE. pH control strategies and supplementation of calcium carbonate were effective in obtaining high IBE titer with high isopropanol production. The analysis of redox cofactor perturbation indicates that the availability of NAD(P)H is the main driving force for the improvement of IBE production.